2004
DOI: 10.1111/j.0032-0862.2004.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and survival of potato scab pathogens (Streptomyces species) on tuber lesions: quick diagnosis based on a PCR‐based assay

Abstract: A time-saving and cost-effective polymerase chain reaction (PCR)-based method was developed for species-specific detection of the scab pathogens (Streptomyces scabies and S. turgidiscabies) prevalent in potato (Solanum tuberosum) in northern Scandinavia. Species specificity of primers was verified using a collection of previously characterized Streptomyces strains isolated from potato scab lesions in Finland and Sweden. A total of 1245 scab lesions was tested from potato cvs Matilda and Sabina grown in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 22 publications
4
90
0
Order By: Relevance
“…Many locations harbored more than one species, and there were isolates from a single lesion belonging to two species. Valkonen's group in Finland has also reported that more than one species can co-inhabit single CS lesions (Lehtonen et al 2004). From these observations, we can conclusively say that pathogenic Streptomyces in single fields and even single lesions are not clonal.…”
Section: Discussionmentioning
confidence: 64%
“…Many locations harbored more than one species, and there were isolates from a single lesion belonging to two species. Valkonen's group in Finland has also reported that more than one species can co-inhabit single CS lesions (Lehtonen et al 2004). From these observations, we can conclusively say that pathogenic Streptomyces in single fields and even single lesions are not clonal.…”
Section: Discussionmentioning
confidence: 64%
“…This is contrary to what we found; tubers showing netted scab symptoms mostly originated from the Western Cape which includes the Sandveld region, known for its sandy soils. It is possible that the lack of a specific geographical species distribution could be due to the use of infected seed tubers or that more than one species could naturally occur in a specific location (Lehtonen et al 2004;Wanner 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Washing tubers and even storing tubers before isolation of the pathogen can result in more S. turgidiscabies than S. scabiei being isolated from the lesions (Lehtonen et al 2004;Valkonen 2004). Dees et al (2013) could only find S. turgidiscabies in a few countries but attributed this to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are important study areas related to plant biotechnology carried out at DAB (Lehtonen et al 2004, 2008a, Mattinen et al 2004, Aittamaa et al 2008, Hiltunen et al 2008, other departments of AF-UH and the Viikki Campus (e.g., Pitkäjärvi et al 2003, Jussila et al 2006, Sjöblom et al 2006. At DAB, these studies are carried out on many crop plant species and their pathogens and also on the model species Arabidopsis thaliana (Karim et al 2007) and the moss, Physcomitrella patens, to understand evolutionary early-developed mechanisms of pathogen defence in plants (Akita and Valkonen 2002, Andersson et al 2005, Lehtonen et al 2006).…”
Section: Molecular Markers and Their Multiple Usesmentioning
confidence: 99%